Peningkatan Pengetahuan Keselamatan Pasien Praoperatif Melalui Edukasi Prinsip 3p Berbasis Fgd - Noor, Sirajudin; Aswadiah, Silvi Yana; Aziz, Luna Rafhifah; Novianti, Syalwa Dwi; Oktaviani, Nita; Hauna, Naula Ajri (Nanggroe: Jurnal Pengabdian Cendikia, 2025)
Patient safety in the preoperative phase is a critical aspect in preventing errors related to patient identity verification, surgical site, and procedural preparation. The community targeted in this program demonstrated limited understanding of the 3P principles (Right Patient, Right Site, Right Procedure). This community service activity employed a pre-experimental one-group pretest–posttest design involving 10 participants who had never received education on preoperative safety. Education was delivered through a Focus Group Discussion (FGD) complemented with leaflets and presentation materials, along with a questionnaire assessing participants’ knowledge of the 3P principles. The results showed a substantial increase in knowledge scores, from an average of 5.6 during the pretest to 9.7 in the posttest, reflecting a 73.21% improvement. All participants experienced an increase in understanding related to preoperative patient safety. This program demonstrates that FGD-based education is effective and has the potential to be integrated as a standard component of community health education to strengthen patient safety culture.